Surface modification of a polyhedral oligomeric silsesquioxane poly(carbonate-urea) urethane (POSS-PCU) nanocomposite polymer as a stent coating for enhanced capture of endothelial progenitor cells - Cousins, Brian G. (2014)
An unmet need exists for the development of next-generation multifunctional nanocomposite materials for biomedical applications, particularly in the field of cardiovascular regenerative biology. Herein, we describe the preparation and characterization of a novel polyhedral oligomeric silsesquioxane poly(carbonate-urea) urethane (POSS-PCU) nanocomposite polymer with covalently attached anti-CD34 antibodies to enhance capture of circulating endothelial progenitor cells (EPC). This material may be used as a new coating for bare metal stents used after balloon angioplasty to improve re-endothelialization. Biophysical characterization techniques were used to assess POSS-PCU and its subsequent functionalization with anti-CD34 antibodies. Results indicated successful covalent attachment of anti-CD34 antibodies on the surface of POSS-PCU leading to an increased propensity for EPC capture, whilst maintaining in vitro biocompatibility and hemocompatibility. POSS-PCU has already been used in 3 first-in-man studies, as a bypass graft, lacrimal duct and a bioartificial trachea. We therefore postulate that its superior biocompatibility and unique biophysical properties would render it an ideal candidate for coating medical devices, with stents as a prime example. Taken together, anti-CD34 functionalized POSS-PCU could form the basis of a nano-inspired polymer platform for the next generation stent coatings.